2020
DOI: 10.1186/s12884-020-2728-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing adoption of facility-assisted delivery - a qualitative study of women and other stakeholders in a Maasai community in Ngorongoro District, Tanzania

Abstract: Background Tanzania’s One Plan II health sector program aims to increase facility deliveries from 50 to 80% from 2015 to 2020. Success is uneven among certain Maasai pastoralist women in Northern Tanzania who robustly prefer home births to facility births even after completing 4+ ANC visits. Ebiotishu Oondomonok Ongera (EbOO) is a program in Nainokanoka ward to promote facility births through a care-group model using trained traditional birth attendants (TBAs) as facilitators. Results to date are promising but… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Thirty-one secondary sources and six interviews informed CMOC5 which relates to families’ ability to overcome barriers impeding their access to MWH-facility birth services. Women and/or families were more likely to have an MWH-birth facility experience if they were able to afford associated costs, such as travel including over long distances or by private vehicle, MWH-facility birth user fees (where applicable) or food and other required supplies 14 91 95 102 104 113 119 125 133. There were instances were women and families reduced their barriers to utilisation by selling assets, borrowing money or incurring debt from the health facility 92 96 114 119.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-one secondary sources and six interviews informed CMOC5 which relates to families’ ability to overcome barriers impeding their access to MWH-facility birth services. Women and/or families were more likely to have an MWH-birth facility experience if they were able to afford associated costs, such as travel including over long distances or by private vehicle, MWH-facility birth user fees (where applicable) or food and other required supplies 14 91 95 102 104 113 119 125 133. There were instances were women and families reduced their barriers to utilisation by selling assets, borrowing money or incurring debt from the health facility 92 96 114 119.…”
Section: Resultsmentioning
confidence: 99%
“…Included studies involved qualitative, quantitative or mixed-methods design (see online supplemental appendix C). Sixty-six sources involved one or more countries in Africa (62.3%),9–15 23 25 28–32 34 36 37 39 42–47 49 77–119 25 involved 1 or more countries in South America (23.6%)8 18 19 21 22 24 26 33 35 40 41 48 50 51 81 120–129 and 7 involved one or more countries from Asia (6.6%) 38 130–135. Eight sources involved multiple continents (7.5%) 16 17 20 136–140…”
Section: Methodsmentioning
confidence: 99%
“…Hence, the authors concluded that, although a leadership empowerment model is desirable, it may be unfeasible to implement in highly hierarchical cultures. Conversely, a recent study among Maasai tribes in Tanzania described the need to rebuild trust among SBAs, TBAs, and the community [32]. That study emphasized that increased sensitivity to women's cultural preferences could close the gap in the trust between these stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…Penghambat peran ayah yang kami temukan adalah stigma sosial. Stigma sosial yang ada mempengaruhi laki-laki untuk tidak ikut dalam proses fertilitas, yang jelas dapat berdampak buruk pada kesehatan ibu (Mosley et al, 2020). Studi ini Rosmadewi & Aliyanto (2022) menemukan faktor kinerja kesehatan yang tidak memuaskan, mecipt pelayanan yang buruk dan perilaku petugas kesehatan yang tidak sopan membuat laki-laki sulit mendampingi istrinya.…”
Section: Faktor Penghambat Peran Ayah Dalam Meningkatkan Kesehatan Ib...unclassified